Description of Personal Factors, Information and Attitudes of Young Women in Early Marriage - Dwi Purwanti (Journal of Global Pharma Technology, 2020)
Introduction: Early marriages are marriages conducted by 18 year olds, who physically, physiologically and psychologically are not yet prepared to take on the responsibilities of marriage, if they are done it can disturb reproductive health. Adolescent problems are a very complex problem ranging from a large number to problems surrounding adolescent reproductive health. Methods: This research is a descriptive quantitative research. The population of this research is all female adolescent of 60 people. The sampling technique was simple random sampling, with a sample size of 30 adolescent female. The variables of this research are personal, information and attitudes. The data collection tool uses a questionnaire, to measure the personal dimension and the dimension of information. Data analysis using descriptive statistics in the form of frequency distribution and central tendency. Presentation of research data in the form of table and textual data. Results: The results of the research on personal factors in adolescent female were 23 (76.7%) women with good personalities, 30 (100%) women with good life values, 23 (76.7%) women with sufficient emotions, and 23 (76.7%) women with good intelligence as much as 21 (70%). Personal factors consisting of dimensions of personality, life values, emotions and intelligence in adolescent female, are 23 (76.7%) women with good personalities, 30 (100%) women with good life values, young women with good emotions. enough as much as 23 (76.7%) and the group of women with good intelligence as much as 21 (70%). The Attitude Toward The Behavioral (Attitude) factor of 28 (93.3%) young women with good beliefs about early marriage and 28 (93.3%) women who have good consequences. Discussion and Conclusion: Three factors in the survey to examine the background of early marriage in ramaja are the personal dimension, the information dimension and the attitude dimension. The description of the results of the three-factor study shows that the numbers need to be taken into account and need to be used as a basis for follow-up in reducing the rate of early marriage among adolescent female.The recommendations offered based on this research are necessary Health care providers should consider a multidimensional approach to supporting and empowering these vulnerable girls. Keywords: Early Marriage, Personal, Information, Attitude.